Clinical management of aggressive fibromatosis/desmoid tumour. (October 2014) - Maruzzo, Marco; Benson, Charlotte; Miah, Aisha; Judson, Ian
<x xml:space="preserve">Abstract</x> Introduction: Aggressive fibromatosis (AF) is a rare benign monoclonal fibroblastic proliferation which accounts for 0.03% of all neoplasms and 3% of all soft tissue sarcomas. It can occur sporadically or within the context of Gardner's syndrome and at any age, although it is more common among young patients. Areas covered: AF is characterised by a natural history that is highly unpredictable; these tumours are benign, in the sense that they do not metastasize, but are locally aggressive, with a high risk of recurrence. Therefore, the management of patients with fibromatosis is challenging and controversial. Surgery, radiotherapy, medical treatment and chemotherapy have been used for AF. Here, the management of AF is reviewed, considering all the known and possible new therapeutic options, in a view of a multidisciplinary management of the patient. Expert opinion: An upfront watchful waiting policy is largely accepted as an initial strategy for management of this disease. Medical treatments should be considered for all the patients who progressed clinically and/or radiologically. The first step should be a hormonal and/or NSAID treatment, followed by systemic chemotherapy or targeted agents. Surgery does play a role where feasible and without undue morbidity, or after other treatment failure. For abdominal wall AF, surgery should be the recommended first-line treatment. As for other rare cancers, careful counselling at a referral centre is mandatory, as well as a multidisciplinary management of the patient.